Guidance and Counseling Management in Home Visit Management in the Digital Era - Utari Pratiwi; Firman; Neviyarni S (Manajia: Journal of Education and Management, 2025)
Home visit is an important strategy in guidance counseling (BK) that aims to understand students' conditions in depth through visits to the family environment. However, its implementation at SMA Negeri 1 Padang faces various challenges, such as time constraints, parental resistance, and logistical constraints. This study aims to identify and provide new ideas and suggestions related to these obstacles and formulate steps to optimize home visits. This research used descriptive qualitative method with the research subject of counseling teachers at SMA Negeri 1 Padang. Data were collected through observation and interviews, then analyzed which included data reduction, data presentation, conclusion drawing, and verification. The results show that home visits help counselors comprehensively understand students' conditions, such as family dynamics, economic factors, and social environment, which affect students' development. However, obstacles such as time constraints, lack of coordination with parents, and lack of resource support are the main challenges. To overcome this, strategic planning, counseling teacher training, and intensive collaboration between the school and family are suggested. The novelty of this home visit activity is through a digital platform. With these steps, home visits can be optimized as an effective tool in counseling management, improve service quality, and support holistic student development.